Ketika Harga Bukan Penentu: Peran Citra Merek dan Social Media Influencer dalam Keputusan Pembelian Kosmetik Lokal - Malikha Fitri; Khotim Fadhli (Business and Economic Publication, 2026)
This study aims to analyze the effects of price, brand image, and social media influencers on OMG lipstick purchase decisions among female students at Universitas KH. A. Wahab Hasbullah. This quantitative study involved 100 respondents selected using purposive sampling, with data collected through a five-point Likert questionnaire. Data were analyzed using SPSS Statistics version 16 through validity, reliability, classical assumption, multiple linear regression, t-test, F-test, and coefficient of determination analyses. The results show that price does not significantly affect purchase decisions (t = 0.708; Sig. = 0.481), while brand image (t = 4.569; Sig. = 0.000) and social media influencers (t = 4.962; Sig. = 0.000) have positive and significant effects. Simultaneously, the three independent variables significantly affect purchase decisions (F = 42.990; Sig. = 0.000), with the model explaining 57.3% of the variance in purchase decisions. The novelty of this study lies in examining these three factors simultaneously among female students of Universitas KH. A. Wahab Hasbullah using OMG lipstick as the research object, while empirically identifying brand image and social media influencers as more influential than price in this research context.